Sustainable agriculture practices and livelihoods in pro-poor smallholder farming systems in southern Africa. Issue 3 (4th May 2017) - Makate, Clifton; Makate, Marshall; Mango, Nelson
Abstract : Climate variability and change threaten and impact negatively on biodiversity, agricultural sustainability, ecosystems, and economic and social structures – factors that are all vital for human resilience and wellbeing. To cope with these challenges, embracing sustainability in food production is therefore essential. Practising sustainable agriculture is one way of ensuring sustainability in pro-poor farming communities in low-income countries. Sustainable agricultural practices are those practices enabling farmers to meet current and future societal needs for food, fibre, ecosystem services and healthy lives. This study evaluates the dynamics of farm-level adoption of sustainable agriculture practices and their effects on maize productivity, crop income and food adequacy, using data from the Chinyanja Triangle in southern Africa. We apply joint estimation techniques to estimate consistently the impact of sustainable agriculture practices on maize productivity, crop income and food adequacy. We established that the uptake of sustainable agriculture practices significantly improves productivity, income and food adequacy. The systematic targeting of reducing gender-related imbalances, enhancing ties to boost access to social capital, diversifying revenue sources to improve wealth and facilitating access to other strategic resources can conclusively enhance the uptake of sustainable agriculture practices, thus improving livelihoods. We recommend the integration of sustainable agriculture practices into rural development policy frameworks in southern Africa.